Fiscal responsibility framework: International experience and implications for Hungary - George Kopits (Magyar Nemzeti Bank, 2007)
In an effort to correct worrisome trends in discretionary fiscal policy (deficit bias, procyclicality, and structural distortions), an increasing number of countries introduced a rules-based fiscal responsibility framework (FRF), characterized by fiscal policy rules, procedural rules, transparency standards, and a surveillance and enforcement mechanism. Preliminary evidence suggests that compliance with a well-designed FRF contributes to building policy credibility, to reducing risk premia, to boosting economic growth, and to lowering output volatility. Faced with large and persistent fiscal imbalances and a sharp buildup of public indebtedness, Hungary would benefit from exploring the adoption a FRF along the following lines. The FRF should encompass the entire public sector, fully accounting for contingent liabilities, and including prudent fiscal projections. Second, it is necessary to strengthen procedural rules, including implementation of the pay-go approach to budget legislation and preparation of a rolling three-year budget program, setting annual limits on the nominal level of primary expenditures. Third, phasing in of a primary surplus rule, calibrated to the path of desired debt reduction, should be seriously considered. Fourth, a current balance rule should be adopted for local self-governments. Finally, compliance with the FRF would need to be monitored by an independent authority.
Keywords: E61; E62; H6; 330; public finances; macroeconomics; Öffentliche Finanzen; Finanzpolitik; Regelbindung; Welt; Ungarn